Odpowiedzi

2009-12-13T16:30:44+01:00
2x+3y=0,5
3x+y= -1 /*(-3)

2x+3y=0,5
-9x-3y=3
--------------dodajemy
-7x=3,5
x=-1/2

3x+y= -1
y=-1-3x
y=-1-3*(-1/2)
y=1/2


metoda podstawiania

2x+3y=0,5
3x+y= -1

2x+3y=0,5
y=-1-3x

2x+3*(-1-3x)=0,5
y=-1-3x

2x-3-9x=0,5
y=-1-3x

-7x=0,5+3
y=-1-3x

-7x=3,5
y=-1-3x

x=-1/2
y=-1-3*(-1/2)

x=-1/2
y=1/2
1 1 1
2009-12-13T16:33:44+01:00
2x+3y=0,5
3x+y= -1 |*(-3)

2x+3y=0.5
-9x-3y=3

2x-9x=0,5+3
-7x=3,5 /(-7)

x=-0,5
-1+3y=0,5 | 3
y= - 0,5
x=0,5


2x+3y=0,5
3x+y= -1

2x+3y=0,5
y=-1-3x

2x+(-1-3x)=0,5
2x-1-3x=0,5
-x=1,5 | * (-)
x= - 1,5
y=-1+4,5

y= 3,5
x=- 1,5




1 1 1
2009-12-13T16:34:33+01:00
Met. podst.:

2x+3y=0,5
3x+y= -1

2x+3y=0,5
y=-1-3x

2x+3(-1-3x)=0,5
y=-1-3x

2x-3-9x=0,5
y=-1-3x

-7x=3,5
y=-1-3x

x=-0,5
y=-1-3x

x=-0,5
y=-1-3*(-0,5)

x=-0,5
y=0,5

met.przeciwnych wspolczynnikow

2x+3y=0,5
3x+y= -1/*(-3)

2x+3y=0,5
-9x-3y=3 +
-----------------
-7x=3,5

x=-0,5

2*(-0,5)+3y=0,5
-1+3y=0,5
3y=1,5
y=0,5

prosze bardzo:)